Money Demand, Exchange Rate, and Remittances in Pakistan: A Vector Autoregressive Analysis - Ghumro, Niaz Hussain; Karim, Mohd Zaini Abd (Economic Journal of Nepal, 2014)
This paper analyzed the relationship between money demand, exchange rate, and remittances incase of Pakistan using annual time series data for theperiod 1972- 2014. The Vector autoregressive methodology has beenemployed to study relationship by analyzing the Granger Causality, Impulse Response Function, and the Variance Decomposition. The results reveal that there is unidirectional causality from remittances to money demand and exchange rate. Based on the impulse response function, a positive shockresults in remittances increase in money demand. It shows that advent of remittances increase income of households and hence, increase inconsumption on goods and services thereby increase in money demand. The negative trend between money demand and exchange rate shows that money demand decreases with the appreciation of exchange rate. It is recommended that exchange rate, remittances and management of monetary aggregates should be tracked in the right process, so that their management can lead inthe direction of economic growth in the country.